Smallholder farmers’ adoption and perception of communally established cattle feedlots for climate change resilience in the Eastern Cape, South Africa - Slayi, Mhlangabezi; Zhou, Leocadia; Jaja, Ishmael Festus (Frontiers in Sustainable Food Systems, 2023)
Introduction This study aimed to assess the willingness and awareness of cattle farmers in the Eastern Cape, South Africa, to participate in communally established feedlots as a climate change adaptation strategy. The research sought to understand the factors that influenced farmers’ willingness to engage in feedlots and their level of awareness regarding the associated benefits and challenges. Methods Data was collected through surveys and interviews with 250 cattle farmers in rural communities, and the findings were analyzed. Results The results revealed that a significant proportion of cattle farmers expressed willingness to participate in communally owned feedlots as a climate change adaptation strategy. Several factors were identified as influencing farmers’ willingness, including age, education level, knowledge level, and awareness level. Younger farmers with higher education levels, greater knowledge about feedlot participation, and higher awareness levels regarding the benefits and challenges were more likely to demonstrate willingness to engage in feedlots. Discussion These findings emphasize the importance of targeted interventions, such as education and awareness programs, to enhance farmers’ willingness and participation in feedlot initiatives. The study also shed light on the key benefits and challenges associated with feedlot participation. The benefits included increased livestock productivity, improved climate resilience, efficient utilization of resources, enhanced market access and profitability, and improved management practices. However, challenges such as initial investment costs, technical knowledge requirements, and potential environmental impacts were also identified. Overall, this study provides valuable insights into the willingness and awareness of cattle farmers regarding communally owned feedlots as a climate change adaptation strategy.